1999
DOI: 10.1002/(sici)1097-4628(19991024)74:4<877::aid-app14>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

?-Irradiated poly(tetrafluoroethylene) particle-filled low-density polyethylene. II. UV stability of LDPE in the presence of 2�-PTFE powder and silane coupling agents

Abstract: Ultraviolet (UV) stability of ␥-irradiated poly(tetrafluoroethylene), 2°-PTFE, powder-filled low-density polyethylene (LDPE) was studied in this work. The mechanical and thermal properties of 2°-PTFE powder-filled LDPE were discussed in our previous work (Akınay and Tinçer, 1999). It already has been shown that silane coupling agents (SCAs) result in improvements in mechanical properties. The UV stability of these samples was followed by a comparision between strain at break measured after UV irradiation and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 7 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…21 Particulate polytetrafluoroethylene added to LDPE increased its resistance to UV radiation. 27 Tensile strength was reduced by one half and toughness by two thirds when polyethylene containing wood flakes was exposed for 205 days. Water absorption and desorption and environmental stress cracking caused the deterioration.…”
Section: Fillers and Reinforcing Fibersmentioning
confidence: 99%
“…21 Particulate polytetrafluoroethylene added to LDPE increased its resistance to UV radiation. 27 Tensile strength was reduced by one half and toughness by two thirds when polyethylene containing wood flakes was exposed for 205 days. Water absorption and desorption and environmental stress cracking caused the deterioration.…”
Section: Fillers and Reinforcing Fibersmentioning
confidence: 99%
“…Zimmerman 25 showed that an extensive autocatalytic reaction by hydrolytic cleavage of polyester chains resulted in carboxyl groups under isothermal heating. Similar results were reported earlier by Buxbaum,26 and the degradation mechanism was also reviewed by Jabarin. 27 Consequently, The silane treatement is expected to facilitate extensive hydrolysis and condensation, also possible alkoxy exchange reactions on the surface of the PET particles.…”
Section: Sem Studiesmentioning
confidence: 99%